2020
DOI: 10.1007/s00709-020-01488-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding leydigioma: do G protein-coupled estrogen receptor and peroxisome proliferator–activated receptor regulate lipid metabolism and steroidogenesis in Leydig cell tumors?

Abstract: Leydig cell tumors (LCT) are the most common type of testicular stromal tumor. Herein, we investigate the G protein-coupled estrogen receptor (GPER) and peroxisome proliferator-activated receptor (PPAR) implication in regulation of lipid homeostasis including the expression of steroidogenesis-controlling molecules in clinical specimens of LCTs and tumor Leydig cells (MA-10). We showed the general structure and morphology of LCTs by scanning electron and light microscopy. In LCTs, mRNA and protein analyses reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 67 publications
(58 reference statements)
5
23
0
Order By: Relevance
“…Low expression of peroxisome-proliferator activated receptor α, β, and γ (PPAR α, β, and γ) was confirmed in the Leydig cell tumor [28] and its regulation by adiponectin was confirmed [48]. Our recent findings showed different morphological types of Leydig cells present in tumor mass [28]. Herein, on ultrathin sections of the tumor, we confirmed also the presence of adipocyte-like cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Low expression of peroxisome-proliferator activated receptor α, β, and γ (PPAR α, β, and γ) was confirmed in the Leydig cell tumor [28] and its regulation by adiponectin was confirmed [48]. Our recent findings showed different morphological types of Leydig cells present in tumor mass [28]. Herein, on ultrathin sections of the tumor, we confirmed also the presence of adipocyte-like cells.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, adipokine signaling proteins were examined to define the role these hormones play and whether there is a potential interaction between adipokines and aromatase. This study is a continuation of our prior reported data [28,29] and provides further knowledge on the biology of Leydig cell tumors.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Consequently, it was also observed that there are alterations in lipid-and cholesterol-associated proteins such as LHR, PKA, PLIN, HSL, StAR, TSPO, HMGCS, and HMGCR, together with the cGMP and PI3K-Akt-mTOR pathways. These changes of expression could be primary disturbances in healthy Leydig cell, and the study of these alterations could be useful to design a new therapeutic approach for Leydig cell tumors [134].…”
Section: Gper Role In Testicular Tumorsmentioning
confidence: 99%
“…Testicular Physiology Testicular Tumors SPG GPER activation induces proliferation [84][85][86] GPER is overexpressed in seminoma and embryonal carcinoma [119], (whereas ERα is missing [120]) GPER mediates estrogen and xenoestrogen-dependent proliferation in seminomas [123][124][125]128,129] SPT GPER activation induces apoptosis [31,32,88] RS GPER activation induces apoptosis [30] LC GPER is involved in: LC morphology and function [38] LCT [where ERα is overexpressed]: GPER activation decrease cell proliferation and induces apoptosis [130] Xenoestrogens decrease GPER expression favoring LCT progression [133] GPER is involved in LCT control of lipid metabolism and steroidogenesis (interaction with PPAR) [134] LC androgens production [40] LC lipophagy inhibition [43] LC miRNA biogenesis [49] LC development and function [PPAR crosstalk] [46] SC GPER activation induces proliferation in immature testis [65][66][67][68] Sertoli cell tumors: GPER is expressed but the role has been not identified. In interstitial compartment, GPER appears to play an important role in regulating estrogen-dependent lipid homeostasis and testosterone biosynthesis that occur in Leydig cells.…”
Section: Cell Typesmentioning
confidence: 99%